Ta’tsīru ath-Tharīqah al-Maḥfūẓāt lit-Tarqiyaty al-Isti‘āb al-Mufradāt fīl Mahārah al-Kalām Ladāy Tullāb - Mahmud Rifa’i; Muhammad Syaifullah; Dian Risky Amalia (CV. Creative Tugu Pena, 2025)
Arabic plays a central role in Islamic education as the language of the Qur’an and Sunnah, serving as a key to comprehending Islamic teachings holistically. This study aims to: (1) describe the implementation of the ṭarīqah al-maḥfūẓāt in Arabic language instruction, and (2) examine its effect on improving vocabulary mastery in speaking skills among seventh-grade students at WaliSongo Islamic Junior High School, Central Lampung. This research employed a quantitative quasi-experimental design involving experimental and control groups. Data were collected through tests, observations, and questionnaires, and analyzed using descriptive and inferential statistical techniques.The results indicate that the memorization method was implemented systematically and effectively. It significantly enhanced students’ vocabulary mastery and speaking skills, with a very strong correlation of 96.0% (r = 0.960; Sig. = 0.000), demonstrating a highly significant effect. These findings confirm that vocabulary mastery is a crucial factor in developing speaking skills. Furthermore, structured memorization supported by understanding and continuous practice contributes substantially to improving students’ language competence. Therefore, this study recommends the balanced application of the memorization method in Arabic teaching and suggests further research involving broader samples and varied methodologies.